Duplex-Specific Nuclease-Enabled Target Recycling on Semiconducting Metal–Organic Framework Heterojunctions for Energy-Transfer-Based Organic Photoelectrochemical Transistor miRNA Biosensing - Gao, Ge; Chen, Jia-Hao; Li, Cheng-Jun; Wang, Cheng-Shuang; Hu, Jin; Zhou, Hong; Lin, Peng; Xu, Qin; Zhao, Wei-Wei (Analytical chemistry (Washington), 2022)
Semiconductor metal–organic frameworks (MOFs) and heterojunctions have gained increasing attention in many fields, yet their full potential remains largely unexplored. Advanced optobioelectronics are envisioned to create more opportunities for innovative biomedical applications. This study reports a UiO-66-NH2 (U6N)/CdS quantum dots (QDs)-gated organic photoelectrochemical transistor (OPECT) and its application toward energy-transfer-based sensitive microRNA-166a (miRNA-166a) detection assisted by duplex-specific nuclease (DSN)-enabled target recycling. Specifically, a U6N/CdS QDs photoanode was fabricated and shown to be efficiently gating a poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT/PSS) channel, while the DSN-enabled release of Au-reporters and hybridization upon the U6N/CdS QDs photoanode could significantly inhibit the photoanode response via an energy transfer process and thus modulate the device response, permitting novel dual-amplified optobioelectronic miRNA-166a detection with a low detection limit of 1.0 fM. This work not only features the DSN-amplified miRNA detection via an OPECT route but also unveils the potential of semiconductor MOF heterojunctions for futuristic optobioelectronics.